Duodenal gangliocytic paraganglioma, successfully treated by local surgical excision-a case report. (2017) - Papaconstantinou, Dimetrios; Machairas, Nikolaos; Damaskou, Vasileia; Zavras, Nikolaos; Kontopoulou, Christine; Machairas, Anastasios
Highlights: Duodenal gangliocytic paraganglioma is a rare tumor usually with benign behavior. Resection of the tumor, either endoscopically or surgically is the treatment of choice. Complete removal of the mass offers cure and long-term survival. Abstract: Introduction: Duodenal gangliocytic paragangliomas are rare neoplasms often arising in proximity to the major duodenal papilla of Vater. These neoplasms are considered to have a benign behavior with lymph node metastases being a rare phenomenon and distant metastatic disease even more so. Resection of the tumor is the only definitive therapy. Presentation of case: A 67 year old male presented to a referring hospital with symptoms of fatigue and malaise. Evaluation with CT imaging revealed a 3.1 cm intraluminal mass situated grossly at the junction of the third with the fourth portion of the duodenum. The tumor was found to be situated near the ampulla of Vater and was excised through a longitudinal duodenotomy followed by myotomy of the sphincter of Oddi. Discussion: Complete resection of duodenal gangliocytic paragangliomas by surgical or endoscopic means is the only potential cure. Endoscopic removal is the first option and is both safe and adequate. Ηowever, localized excision may be utilized instead in those cases in which endoscopic removal is not possible or cannot achieve negative margins. Recurrent disease after complete resection is unlikely. Conclusion: Cases of duodenal gangliocytic paragangliomas are best managed with endoscopic resection. However, local surgical excision remains as a second-choice procedure. Adjuvant chemotherapy and radiotherapy are unnecessary after complete excision.